Pengaruh Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), dan Intellectual Capital Disclosure (ICD) Terhadap Nilai Perusahaan pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2023-2024 - Rohma Hasanah; Ati Sumiati; Dwi Kismayanti Respati (Teewan Journal Solutions, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Intellectual Capital Disclosure (ICD) on firm value in companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) for the 2023–2024 period. CSR is measured using a CSR index based on GRI standards, GCG is proxied by institutional ownership, and ICD is measured using a four-level numerical coding method. Firm value is assessed using the Tobin’s Q ratio. This research employs a quantitative method with an associative approach and multiple linear regression analysis. The sample consists of LQ45 companies selected through purposive sampling. The results show that partially, GCG and ICD have a significant positive effect on firm value, while CSR has a significant negative effect. Simultaneously, the three independent variables have a significant influence on firm value. This study implies that companies should enhance the disclosure of GCG and ICD as a strategy to improve firm value